2013
DOI: 10.1523/jneurosci.3319-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for Macrophages Near Axotomized Neuronal Cell Bodies in Stimulating Nerve Regeneration

Abstract: Macrophages have been implicated in peripheral nerve regeneration for some time, supposedly through their involvement in Wallerian degeneration, the process by which the distal nerve degenerates after axotomy and is cleared by phagocytosis. Thus, in several studies in which macrophage accumulation in the distal nerve was reduced and Wallerian degeneration inhibited, regeneration was delayed. However, this interpretation ignores the more recent findings that macrophages also accumulate around axotomized cell bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
169
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(185 citation statements)
references
References 64 publications
(17 reference statements)
12
169
1
Order By: Relevance
“…This inadequate axon regrowth led to the suggestion that, although regeneration would eventually proceed, albeit slowly, a rapid course of Wallerian degeneration is necessary if axons are to regenerate at optimal rates and maximum extent (41). More recently, Niemi et al (42) found that, in addition to delayed Wallerian degeneration, reduced PNS regeneration in injured Ola animals seems to be related to defects at the level of the neuronal cell body, because neurite outgrowth is impaired if macrophages and their products are reduced or absent. This idea of early PNS injury events impacting later processes extends to other functions, such as Schwann cell redifferentiation and remyelination.…”
Section: Discussionmentioning
confidence: 99%
“…This inadequate axon regrowth led to the suggestion that, although regeneration would eventually proceed, albeit slowly, a rapid course of Wallerian degeneration is necessary if axons are to regenerate at optimal rates and maximum extent (41). More recently, Niemi et al (42) found that, in addition to delayed Wallerian degeneration, reduced PNS regeneration in injured Ola animals seems to be related to defects at the level of the neuronal cell body, because neurite outgrowth is impaired if macrophages and their products are reduced or absent. This idea of early PNS injury events impacting later processes extends to other functions, such as Schwann cell redifferentiation and remyelination.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings, others have shown a beneficial role for CCR2 in a model where CCR2-dependent macrophages were critical for nerve regeneration following axotomy. 60 It is possible that CCR2 plays different roles depending on the site and mechanism of injury. A greater understanding of the mechanisms, cellular subsets, timing, and environmental cues should clarify our understanding of this molecule and of the cells on which it is expressed.…”
Section: Discussionmentioning
confidence: 99%
“…dorsal root ganglion | transcription factor | axotomy | sensory neuron A complex series of cellular and molecular events participates in reprogramming sensory neurons as they transition to a regenerating state following peripheral nerve injury (1)(2)(3)(4)(5)(6)(7). Injury discharge and rapid ion fluxes initiate this transition, followed by the loss of target-derived signals and receipt of retrograde signals from the site of injury (8)(9)(10).…”
mentioning
confidence: 99%